Implementation of Grade 8 Science Curriculum 2012 in Bangladesh: Challenges and Way Forward - Hossain, Mohammed Zakir (Journal of Education and Research, 2019)
This paper identifies the challenges encountered by the Science teachers in implementing Science Curriculum 2012 at Grade 8 and search the effective way forwards to minimize the challenges. The mixed method research design was employed. The population of this study was the Grade 8 Science teachers in Bangladesh. A set of survey questionnaire and interview schedule each was used for data collection. Data collection tools were reviewed by science curriculum experts and pre-tested by Grade 8 science teachers. Descriptive statistics was used for survey data interpretation. To interpret the findings, both qualitative and quantitative data were triangulated. The challenges identified by the Grade 8 Science teachers were unfriendly textbook, inadequate physical and instructional facilities, lack of teachers' professional skills, irregular in-service trainings, inefficient instructional monitoring and mentoring system. The way forwards were introducing regular professional development initiatives, upgrading instructional facilities, improving the physical environment, updating Grade 8 Science textbook and establishing a continuous instructional monitoring and mentoring system.